IMPLEMENTASI COMMUNITY BASED TOURISM PADA WISATA RELIGI DI TULUNGAGUNG - Ihsani, Fathul (TARBAWI:Journal on Islamic Education, 2023)
This research aims to explore the management of religious tourism based on Community Based Tourism (CBT) in creating a deep spiritual experience using a neuroscience approach for pilgrims in Tulungagung Regency. The research method used is a qualitative method with an ethnographic approach, involving direct observation, in-depth interviews with stakeholders, and analysis of related documents.Tulungagung Regency has great potential in religious tourism with various sites that are pilgrimage destinations, such as the Tomb of Sheikh Basyarudin and Sunan Kuning which is currently being researched by the author. The CBT concept is usually often applied in conventional tourism management which prioritizes material profits and the welfare of the surrounding community. In this case, researchers try to study the implementation of CBT in the religious tourism sector where the aspect of material gain is not the main goal. Through the CBT approach, this research found that the active participation of local communities in the management and development of religious tourism not only improves the local economy but is also able to improve the neuroscience spiritual experience of pilgrims.The research results show that the integration of CBT-based management with a neuroscience approach can create a deeper and more measurable spiritual experience. Pilgrims who carry out the Wirit Ritual, Meditation, Collective Prayer and Healing Ritual produce the Pilgrim's spiritual experience. With unique site management, driving figures, involvement of the wider community as the main tourism actors; Facilitating aid funds for existing embryonic activities, links to relevant stakeholders are some of the strategies identified as keys to the success of managing CBT-based religious tourism in Tulungagung Regency.This research concludes that the CBT-based religious tourism management model is effective in creating a deep spiritual experience for pilgrims while providing a positive impact on the social and economic desires of local communities. Recommendations are given to local governments and other stakeholders in adopting this approach for the development of religious tourism destinations in other regions